Toward a Theory of the Arts and Sustainability - BERTAUX, NANCY (Archīum Ateneo, 2017)
To make real progress on what can only be classified as environmental emergencies, we need a wide base of public consensus for action given that public motivation and involvement is a prerequisite for policymakers to implement what our scientists urge us to do. In this light, crucial thresholds of public motivation and involvement can be created by reaching into the hearts of individuals, an area of competitive advantage for the arts. Efforts to enhance understanding in this arena, however, must incorporate sufficient complexity given highly complex and inter-related challenges in sustainability. This article thus presents a theoretical framework for the arts and sustainability based on the variables of artistic complexity and public engagement. The arts, when allowed sufficient scope and freedom, can assist society in marshalling and galvanizing people across the globe to take essential steps toward a sustainable planet.